Felino Molina and Sara Molina interviewed by Rob Willis in the Rob and Olya Willis folklore collection. - Molina, Felino, 1957-; Molina, Sara; Willis, Rob, 1944-; Willis, Olya (2017)
Folkloric recording.
Recorded with Olya Willis.
Recorded on 19 May 2017 in Darwin, Northern Territory.
Timed summary available.
Keywords: Molina, Felino, -- 1957- -- Interviews; Molina, Sara -- Interviews; Filipino Australians -- Northern Territory -- Darwin -- Interviews; Musical theater producers and directors -- Northern Territory -- Darwin -- Interviews; Musicians -- Northern Territory -- Darwin -- Interviews; Educational consultants -- Northern Territory -- Darwin -- Interviews; Electrical engineers -- Northern Territory -- Darwin -- Interviews; Computer programmers -- Northern Territory -- Darwin -- Interviews; Musical directors